A Practical and Highly Efficient Procedure for the Synthesis of the Trifluoromethylpyrazol-Derived Canonical Transient Receptor Potential Channel (TRPC3) Inhibitor Pyr3 and Its Derivatives - Wu, Zhongzhi; Li, Wei (Synlett, 2025)
Canonical transient receptor potential (TRPC) channels play a variety of diverse biological functions. Among the subgroups of the TRPC family (TRPC3, TRPC6, and TRPC7), TRPC3 has been implicated in several diseases, including neurological and cardiovascular diseases, cancer, and neurodegeneration. A pyrazole-based compound Pyr3 is a selective TRPC3 channel inhibitor which is now a standard tool compound to study conditions associated with TRPC3 dysregulation. However, the reported literature syntheses of Pyr3 either provided low yield or involved microwave reactions and harsh reaction conditions. We have developed a practical and highly efficient procedure for the synthesis of Pyr3 and its derivatives in high yields which is suitable for scale-up synthesis.
Keywords: TRPC3; ion channel inhibitor; Pyr3; pyrazole synthesis; acylation